Optimum use of irrigation water: Bioeconomic household modeling of small-scale irrigation scheme in South Central Ethiopia - Adela, Fitsum Assefa; Justus Liebig University Giessen (My University, 2023)
The Ethiopian economy is agrarian, by and large. This is evidenced by the fact that the agricultural sector contributes nearly 36 percent of the GDP and employs 80 percent of the population. However, the sector’s growth has been impended by institutional, environmental and other factors. The sector is dominated by smallholders who are vulnerable to external shocks and have limited capacity to invest on their land. This causes low productivity to prevail in the sector, which further exacerbates the prevalence of rural poverty. In recent times, the government of Ethiopia promotes the expansion of small- scale irrigation by optimally using the bounty of water resources in a bid to reducing poverty and food insecurity. But, many of the surface water are dominated by rivers (both small and big) which flow cross different localities. The rivalry in using the water across the course of the river causes continual conflict among communities living on different courses of the river. In the study area, there is a small river that passes through upstream, middle stream and lower stream localities; and there is conflict among users along the way. Despite the prevalence of such burning issues, studies on the optimal allocation of water and on the impact of irrigation on poverty using rigorous economic models are scanty except some that have rather focused on identifying factors urging households to use irrigation. This justifies the need for examining the extent to which the flowing water is optimally shared among users across the course of the river in a way that brings maximum benefits. Against the backdrop of the aforementioned gaps, this study is, therefore, an attempt to bridge the observed gaps by using both bioeconomic and econometrics approaches. Data have been collected from 240 households, which live in upper, middle and lower parts of the stream. The descriptive results have shown that there is significant difference in the socio-economic characteristics between farmers who have access to irrigation and those who do not. Poverty analysis was conducted using the Foster–Greer–Thorbecke (FGT) indices based on own constructed consumption poverty line. The incidence, depth, and severity of poverty were found to be higher among farmers who do not have access to irrigation. Assessment of the physical irrigation infrastructure indicated performance problems of the canals and a significant amount of water loss during transportation. Irrigation is undertaken in turns based on a schedule set by Water Users Association committee. There is also a clear difference in production patterns between households living in upstream, middle stream and lower stream parts of the river. Those households which live in the upper stream produce more Khat than households living either in the middle or lower stream. In fact, in relative terms, those households which live in the middle parts of the river produce more Khat than households living in the lower stream. In the same pattern, the amount of water used per ha by households in the upper stream is by far greater than the amount of water used per ha by households in the lower parts of the river both for Khat and sugar cane production. This could be associated to the location advantage upper stream households have to access more water. The results of the logistic regression showed that institutional set ups and governance of the irrigation scheme, access to information and social network, and water scarcity level have significant impacts on farmers’ decisions to irrigate. Among the factors, the pesticide amount used, and landholding size have a positive and significant impact on the farm income of the respondent households. Plot size and distance to nearest market, on the other hand, have a negative and significant impact on farm income of households. Regarding per adult equivalent food consumption, households’ farm income, non-farm income, and household asset have positive and significant impacts. Household size and dependency ratio, on the other hand, have a negative impact. Further analyses were carried out using bioeconomic modeling in order to identify alternative policies that ensure optimal water allocation along the stream. There are two cash crops (sugarcane and Khat) that are produced in the study area. Khat consumes more water than sugarcane and has undesired socio economic impacts. This situation requires interventions to be designed to reduce the production of Khat such that the water could be optimally allocated across the course of the river. Towards this end, three scenarios were considered for simulations namely improving the efficiency of water use and taxing Khat production, water tax and allocating more land to Sugarcane were considered. Improving efficiency of sugarcane production and taxing Khat improves the production of sugarcane. Water pricing promotes the production of khat, while land allocation promotes the production of sugarcane. Based on the aforementioned analysis, the study pinpointed the fact that both institutional and social factors should be given prime attention to ensure fair distribution of water across the course of the river and to instigate farmers to use irrigation. Besides, enhancing the productivity of sugarcane through improved technology should be the main concern of stakeholders. In this regard, a system that tends to enhance the productivity of sugarcane should be in place such that the community would allocate more land to sugarcane which eventually ensures sustainable water use across the course of the river ultimately benefiting users.
Keywords: optimum water use; small scale irrigation; bio-economic household model; Ethiopia; ddc:330; ddc:333.7